Ten missteps in the management of inflammatory bowel disease in Asia: An expert report by the Asian Pacific Association of Gastroenterology Working Group on Inflammatory Bowel Disease - Vineet Ahuja; Ida Hilmi; Byong Duk Ye; Khoon Lin Ling; Siew C. Ng; Rupert W. Leong; Peeyush Kumar; Xin Hui Khoo; Govind K. Makharia; Jose Sollano; Pises Pisespongsa; Nazri Mustaffa; et al. (My University, 2024)
Abstract Inflammatory bowel disease (IBD) is rapidly emerging in the Asia Pacific region. However, there are many challenges in the diagnosis and management of this condition. The Asian Pacific Association of Gastroenterology (APAGE) Working Group on IBD conducted a round table meeting to identify 10 common mistakes in the management of IBD in Asia. To summarize, many physicians still over rely on a definitive histological diagnosis before starting treatment and do not fully establish disease extent such as perianal and proximal gastrointestinal involvement in Crohn's disease (CD) or extent of involvement in ulcerative colitis (UC). It is also essential to actively look for evidence of extra‐intestinal manifestations, which may influence choice of therapy. In terms of conventional therapy, underuse of topical 5 aminosalicylates (5‐ASAs) in UC and inappropriate dosing of corticosteroids are also important considerations. Acute severe UC remains a life‐threatening condition and delay in starting rescue therapy after inadequate response to intravenous steroids is still common. Anti‐tumor necrosis factors should be considered first line in all cases of complex perianal fistulizing CD. Most patients with IBD are on potent immunosuppressive therapy and should be screened for latent infections and offered vaccinations according to guidelines. Under‐recognition and management of significant complications such as anemia, osteoporosis, malnutrition, and thromboembolism should also be addressed. Colonoscopy is still not properly performed for dysplasia/cancer surveillance and for evaluating post‐op recurrence of CD. Another common misstep is inappropriate withdrawal of medications during pregnancy leading to increased complications for the mother and the newborn.
Keywords: Inflammatory Bowel Disease